1978
DOI: 10.1159/000264935
|View full text |Cite
|
Sign up to set email alerts
|

The Role of DNA damage, its Repair and its Misrepair in the Etiology of Cataract: a Review

Abstract: A hypothesis is presented regarding the importance of desoxyribonuclei acid (DNA) repair for maintenance of lens clarity. It is proposed that unrepaired or incorrectly repaired damage to lens epithelial cell DNA may result in decreased lens transparency either by altering normal metabolism in the epithelium or subsequently by affecting lens cell differentiation and protein synthesis in the lens cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…I have discussed elsewhere that there may be a causal relationship between DNA damage and cataracts (3). Because of this relationship and the reported connection between chlorpromazine and lens opacification, I studied chlorpromazine's effect on DNA; I showed that this compound induces unscheduled DNA synthesis in rat lens epithelial cells after light exposure (4), which is consistent with the above hypothesis.…”
supporting
confidence: 59%
“…I have discussed elsewhere that there may be a causal relationship between DNA damage and cataracts (3). Because of this relationship and the reported connection between chlorpromazine and lens opacification, I studied chlorpromazine's effect on DNA; I showed that this compound induces unscheduled DNA synthesis in rat lens epithelial cells after light exposure (4), which is consistent with the above hypothesis.…”
supporting
confidence: 59%
“…With respect to the mechanisms, finally leading to lens opacifications, effects on the DNA of the epithelial cells in the germinative zone and at the anterior lens pole [7,8] as well as posttranslational alterations of already ex isting protein molecules [9,10] are likely to contribute.…”
Section: Introductionmentioning
confidence: 99%
“…Other proteins were detected but have yet to be characterized in the lens epithelial cells of younger as well as aged animals. Eye lens opacification may also be ascribed to misrepair [13]. One might speculate that the alterations o f A D P ribosylation mechanisms are involved in cat aract formation.…”
Section: Discussionmentioning
confidence: 99%
“…C a 2\ M g2+-endodeoxyribonuclease, topoisomerase I, and the A D P R T itself [10][11][12], U V radiation and free radicals produce breaks in D N A and thus may increase A D P R T activity. Moreover, it has been sug gested that U V radiation and free radicals are also involved in lens aging and cataract formation [13]. Therefore, it was o f interest to follow the A D P ribosylation reaction in the lens during aging.…”
Section: Introductionmentioning
confidence: 99%